ANALISIS DETERMINAN KEMISKINAN SEBELUM DAN SESUDAH DESENTRALISASI FISKAL - USMAN -; BONAR M. SINAGA; HERMANTO SIREGAR (SOCA: Jurnal Sosial Ekonomi Pertanian, 2006)
Understanding about determinant factors of poverty will help policy maker to ensurethat the poor get benefit from the economic policy. In general, this study aim toanalyze the changes of determinant factors of poverty before and after theimplementation of fiscal decentralization. Using the model, this study found that incommunity factor there are some variables have change from 1999 to 2002. One ofthese variables is road infrastructure. In 2002 (after fiscal decentralization period),the quality of road was worse than before so the impact is the poverty was increase.This study shows that if both central and local government concern with povertyreduction then they have to notice some sectors such as agriculture, education, familyhealth, and infrastructure. These variables are the determinant factors of poverty.